C(sp(3))-F, C(sp(2))-F and C(sp(3))-H bond activation at silicon(II) centers - Swamy, V. S. V. S. N.; Parvin, Nasrina; Raj, K. Vipin; Sen, Sakya S. (Chemical Communication, 2017)
Silylene [PhC(NtBu)(2)SiN(SiMe3)(2)] (1) cleaves the C(sp(3))-H and C-F bonds of acetophenone and 1,1,1-trifluoroacetophenone, respectively, under mild conditions. The reaction is initiated via a nucleophilic attack from the oxygen to the silicon atom followed by C-F/H bond cleavage. The scope of C-F bond activation has further been extended with C6F6 and C6F5CF3.
Keywords: Boron triple bond; C-F Bond; Fluorinated Building-Block; H Activation; Ketones; N-heterocyclic carbenes; Oxodative Addition; Perfluorinated Arenes; Selective Activation; Transition-Metal Centers

Strikingly diverse reactivity of structurally identical silylene and stannylene - Parvin, Nasrina; Dasgupta, Rajarshi; Pal, Shiv; Sen, Sakya S.; Khan, Shabana (Dalton Transactions, 2017)
The reactivity of structurally identical silylene and stannylene [PhC(NtBu)(2)EN(SiMe3)(2)] (E = Si (1) and Sn (2)) towards coinage metals has been explored. While 1 has the propensity to form an adduct with coinage metals (4 and 5), 2 undergoes a ligand exchange reaction with copper halides and silver triflate leading to PhC(NtBu) 2SnX (X = Br (6), Cl (7), and OSO2CF3 (8)) with concomitant formation of [M{N(SiMe3) (2)}] (M = Cu, Ag). However, with AgSbF6 both 1 and 2 led to ion pairs, 9(+) .SbF(6)(-)and 10(+) . SbF(6)(-)displaying weaker Ag center dot center dot center dot center dot F interactions in the latter.

Diverse reactivity of NOBF4 towards silylene, disilene, germylene and stannylene - Parvin, Nasrina; Sen, Nilanjana; Muhasina, Puthan Veetil; Tothadi, Srinu; Parameswaran, Pattiyil; Khan, Shabana (Chemical Communications, 2021)
{The reactivity of NOBF4 towards silylene, disilene, germylene, stannylenes has been described. Smooth syntheses of compounds of composition [PhC(NtBu)(2)E(= O -> BF3)N(SiMe3)(2)

Reactivity of (TMS)(2)N(eta(1)-Cp*)Si=Si(eta(1)-Cp*)N(TMS)(2) toward the Halides of Groups 13-15 - Sen, Nilanjana; Parvin, Nasrina; Tothadi, Srinu; Khan, Shabana (Organometallics, 2021)
In this paper, we have demonstrated the unique reactivity of a previously reported disilene [(TMS)(2)N(eta(1)-Me5C5)Si=Si(eta(1)-Me5C5)N(TMS)(2)] (1) with the halides of groups 13-15, which resulted in the formation of silicon-E (E = B, Al, Ge, P) bonds. Treatment of 1 with Lewis acidic BCl3 led to the formation of a cationic boron species [Cp*BSi(Cl)(2)N(TMS)(2))][BCl3SiCl3] (2). In contrast, the reaction of 1 with BCy2Cl afforded an oxidative addition product [(TMS)(2)N(eta(1)-Me5C5)Si(BCy2)(Cl)] (3) via the insertion of a Si(II) atom into the B-Cl bond. Extending the reaction with its higher congener led to classical Lewis acid-base adducts, (TMS)(2)N(eta(1)-Me5C5)Si -> AlCl3 (4) and (TMS)(2)N(eta(1)-Me5C5)Si -> AlBr3 (5), respectively. The reaction of GeCl2 with 1 proceeded in a completely different manner and resulted in a hybrid dendrimeric compound [HGe(Si(Cl)(2)N(TMS)(2))(3)] (6), whereas, with SnCl2, it led to Cp*SnCl (7). Lastly, the reaction of Ph2PCl followed the same pattern like Cy2BCl and led to the formation of an oxidative addition product [(TMS)(2)N(eta(1)-Me5C5)Si(PPh2)(Cl)] (9) with a Si-P bond.

Synthesis and application of silylene-stabilized low-coordinate Ag(I)-arene cationic complexes - Parvin, Nasrina; Sen, Nilanjana; Tothadi, Srinu; Muhammed, Shahila; Parameswaran, Pattiyil; Khan, Shabana (Organometallics, 2021)
We report the first examples of N-heterocyclic silylene-stabilized monocoordinate Ag(I) cationic complexes weakly bound to the free arene rings (C6H6, C6Me6, and C7H8). Further, the application of these electrophilic Ag(I) complexes as catalysts has been investigated toward A(3)-coupling reactions, which afforded a series of propargylamines in good to excellent yields with low catalyst loading under a solvent-free condition (19 examples).

Hybrid silylene-Pd catalyst: efficient C-N cross-coupling of sterically bulky amines and chiral amines - Kaulage, Sandeep H.; Parvin, Nasrina; Khopade, Kishor V.; Khan, Shabana (Chemical Communications, 2024)
Herein, we report a catalytic system with N-heterocyclic silylene (NHSi)-phosphine-based hybrid bidentate ligands [PhC(NtBu)2SiN(PR2)(2,6-iPr2-C6H3)] and Pd(dba)2, which serves as an effective catalyst for C-N cross-coupling of a wide range of sterically bulky amines and optically active amines, which is challenging otherwise. Herein, we report a hybrid silylene-based bidentate ligand (SiNP)-Pd(0) catalytic system, which performs the C-N coupling of difficult substrates, e.g., sterically bulky amines and chiral amines.